VITAMINS WITH ANTIOXIDANT EFFECTS IN PROPHYLAXIS AND TREATMENT OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN - E. V. Shikh (Вопросы современной педиатрии)
Natural antioxidants can be used in prophylaxis and treatment of respiratory infections in frequently ill children. When administered together, vitamins and antioxidants have synergetic action, which allows not to use dosages, exceeding physiological daily requirements. Provitamin A, vitamins E and C are the part of specialized complex for children, which along with antioxidant action, has immunomodulatory, anti-inflammatory and adaptogenic effects. β-carotene does not dissolve in water and its oil solutions have very low concentration (< 0,1%), hence its assimilation from pelleted forms and oil solutions significantly depends on alimentary fats content and condition of the digestive tract. Water solubility of the studied drug provides high degree of the assimilation of active substances. Liquid form for oral administration is convenient for dosing and can be used in infants. The presented analysis of clinical trials showed, that usage of antioxidant complex led to health and functional state improvement, appetite and sleep normalization. The markers of non-specific immune protection improved in the majority of children, which correlates with decrease of prevalence and duration of diseases. Such microelements as zink and selenium can also be used as general-stimulating and immunomodulatory components. There are publications, confirming efficacy of vitamin and mineral complexes usage in order to lower the risk of acute respiratory tract infection, in the medical literature.